Analysis of the Effect of Product Quality, Service Quality and Brand Image on Samsung Smartphone Purchase Decisions: Analisis Pengaruh Kualitas Produk, Kualitas Pelayanan dan Citra Merek Terhadap Keputusan Pembelian Smartphone Samsung - Safitri Budi Hermawan; Slamet Harjatno (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study was to analyze the effect of product quality, service quality and brand image on purchasing decisions for Samsung smartphones partially and simultaneously for students of the Faculty of Business, Law and Social Sciences UMSIDA. This study uses a quantitative research approach. The population of this study were students of the Faculty of Business, Law and Social Sciences UMSIDA. The research sample was obtained using a stratified random sampling technique that is calculated using the Slovin formula, which is as many as 100 respondents. The research data were obtained using a questionnaire technique and analyzed by multiple linear regression analysis. The results showed that product quality, service quality and brand image had a positive and significant effect partially and simultaneously on purchasing decisions for Samsung smartphones for students of the Faculty of Business, Law and Social Sciences UMSIDA. Highlights: Product quality, service quality, and brand image influence purchasing decisions for Samsung smartphones among UMSIDA students. Quantitative research approach with 100 respondents from the Faculty of Business, Law and Social Sciences. Multiple linear regression analysis reveals a positive and significant effect of product quality, service quality, and brand image on purchasing decisions. Keywords: product quality, service quality, brand image, purchasing decisions, Samsung smartphones